ANALISIS SENYAWA KIMIA Dryobalanops aromatica - Gunawan Pasaribu; Gusmailina; Sri Komarayati; Zulnely; Erik Dahlian (Jurnal Penelitian Hasil Hutan, 2014)
Dryobalanops aromatica is a woody plant that produces non timber forest product such oil and crystal. Thechemical composition information is important for oil utilization and specific marker of the material. Traditionally, oilquality was grouped based on its colour. The whiter the colour, the better the quality. This paper examines the chemicalcontent of four oil groups and two kinds of crystal. The examination was carried out in Gas Chromatography MassSpectrometry (GCMS). The results show that the oil of Dryobalanops aromatica 1 contains borneol up to 26.02%, D. aromatica 2 contains 13.95%, D. aromatica 3 contains 24.03%, and D. aromatica 4 contains 1.09% in longiborneol form. Meanwhile, crystal 1 contains 92.70% of borneol and crystal 2 contains 90.73%. Borneol compoundcan act as chemical marker of Dryobalanops aromatica.